Characteristics and postoperational outcomes in paediatric patients with coronary sinus septal defect: a retrospective cohort study - Pang, Chengcheng; Wang, Huimin; Shen, Junjun; Yang, Liuqing; Li, Jianglin; Liu, Hui; Pan, Wei; Zhang, Zhiwei (Cardiology in the young, 2025)
To summarise the characteristics and postoperative outcomes in paediatric patients with coronary sinus septal defect. This retrospective study recruited paediatric patients diagnosed with coronary sinus septal defect from the Guangdong Cardiovascular Institute between 2011 and 2023. Clinical characteristics, echocardiographic parameters, surgical procedures, and postoperative outcomes were collected from electronic health records. Among the 68 patients, 50% were male, with a median age of 1.0 years. Four cases (5.9%) were diagnosed during the prenatal period. The proportions of patients with type I, II, III, and IV coronary sinus septal defect were 51.5%, 5.9%, 16.1%, and 26.5%, respectively. The most common coexisting cardiac anomalies were persistent left superior caval vein. Twenty-seven cases were either missed or misdiagnosed by echocardiogram, accounting for 39.7% of the overall cases, with type I being the most frequently missed diagnosis. Fifty-four patients underwent surgery, two patients received transcutaneous intervention, while the remaining patients did not undergo any surgery or intervention. At follow-up, two patients with type I coronary sinus septal defect died from multiorgan dysfunction, and one patient underwent reoperation due to narrowing of the extracardiac tunnel. The remaining patients did not experience any major events and recovered well. Paediatric patients with coronary sinus septal defect often do not exhibit specific clinical manifestations. Enhancing our understanding of the anatomic and haemodynamic characteristics of coronary sinus septal defect can improve the diagnostic accuracy of echocardiography. If diagnosis is suspected, confirmation can be obtained by cardiac CT and cardiac magnetic resonance. Accurate preoperative and intraoperative diagnosis of coronary sinus septal defect contributes to high surgical success rates and favourable treatment outcomes.